When will China fulfill its carbon‐related intended nationally determined contributions? An in‐depth environmental Kuznets curve analysis. Issue 5 (5th August 2020) - Meng, Ming; Shang, Wei; Wang, Xinfang; Pang, Tingting
Abstract: Considering the enormous amounts of carbon dioxide (CO2 ) emissions generated in China, the country's fulfillment of its Intended Nationally Determined Contributions (INDCs) is essential in achieving the goal of mitigating global climate change delineated in the Paris Agreement. In order to forecast the future development of China's carbon‐related INDC indicators, this research uses a segmented quadratic equation to fit the relationship between economic level and CO2 emissions and a hybrid trend extrapolation model to forecast the emission‐related indicators. The empirical analysis shows that China's CO2 emission peak appeared in 2018 with an emission amount of 9.36 billion tons. The future CO2 emissions after 2018 will present a fluctuating and slowly decreasing trend. As to the carbon intensity, China will meet the INDC target (lower by 60–65% from the 2005 level) in 2022–2023. At that time, China's CO2 emissions will be 8.43–7.96 billion tons and GDP will reach 109.71–125.39 trillion yuan. Furthermore, the empirical analysis also shows that even if China's carbon intensity target is successfully realized, it will still have considerable potential for further reduction. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.